POTENSI PENGHEMATAN BIAYA TAGIHAN LISTRIK PASCA PEMASANGAN PLTS ATAP GEDUNG RUSUNAWA UNIVERSITAS UDAYANA - Widiandika Putra, I Wayan Dicky; Ariastina, Wayan Gede; Dwi Giriantari, Ida Ayu; Setiawan, I Nyoman; Sukerayasa, I Wayan; Satya Kumara, I Nyoman (Jurnal SPEKTRUM; Vol 10 No 4 (2023): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2023.v10.i04.p12, 2023)
The limited availability of natural resources and the impact on the environment that regularly using fossil-based electricity become the basis for the government to develop renewable energy. One of the potential uses of renewable energy in Indonesia is a rooftop solar power plant which in its design does not require a large area of land and space for the placement of solar modules. This research designing rooftop solar power plants with an on-grid system on the Udayana University Rusunawa building with the capacity scenario of 20 kWp, 15 kWp, and 10 kWp using HelioScope. Based on the results of rooftop solar power plants production can be seen the potential cost savings of electricity bills each year. Based on the results of the design for rooftop solar power plants scenario, the number of solar modules obtained is 40 pieces, 30 pieces and 20 pieces with potential savings in electricity bill costs of Rp. 33.391.515, Rp. 28.933.478 and Rp. 23.269.285 per year.